Predictors, patterns and outcomes following Infective endocarditis and stroke : Outcomes following Infective endocarditis and stroke - Mishra, Ajay; Sahu, Kamal Kant; Abraham, Benson Mathew; Sargent, Jennifer; Kranis, Mark J; George, Susan V; Abraham, George (Acta Biomedica Atenei Parmensis, 2022)
Patients with infective endocarditis can have multiple neurological manifestations.  Cerebrovascular events (CVE) in patients with IE can be hemorrhagic or embolic.  Multiple factors are known to predispose to CVE and increased mortality in patients with IE.  In this study, we aimed to describe various outcomes among patients with IE and CVE.  We retrospectively analyzed 160 patients with definite IE.  Among these, patients with radiological evidence of CVE were included.  Clinical, radiological, echocardiographic details were obtained.  Outcome studied were the requirement of intensive care unit care, the requirement of mechanical ventilation, prolonged course of antibiotics, prolonged duration of hospital stay, the requirement of surgical intervention, and mortality.  In this study, 16 [10%] of patients with IE were identified to have a CVE.  The mean age of the patients was 55, and 87.5% of them were male.  25% of patients had prior IE.  IE involving left-sided valves were predominant, with the involvement of mitral valve reported in 62.5% of patients.  More than half of the patient's had details of magnetic resonance imaging (MRI) of the brain.  CVE were mostly ischemic, anterior circulation predominant, multiple, and bilateral.  In patients with IE and CVE morbidity including the requirement of ICU care, prolonged antibiotics course, and the requirement of surgical intervention contributed to increased duration of hospital stay.  In conclusion, CVE in patients with IE tends to present as multiple infarcts predominantly located over anterior circulation.  IE patients with CVE tend to have higher morbidity and mortality.